Implication of grain boundary engineering on high temperature hot corrosion of alloy 617. (May 2016) - K., Deepak; Mandal, Sumantra; C.N., Athreya; Kim, Dong-Ik; de Boer, B.; V., Subramanya Sarma
Highlights: Grain boundary engineered microstructure achieved in alloy 617 by strain annealing. Grain boundary engineered microstructure showed improved resistance to hot corrosion. Cr depletion at grain boundaries observed in non grain boundary engineered sample. S segregation occurred at random high angle boundaries. Abstract: The role of grain boundary engineering (GBE) on high-temperature hot corrosion behavior of alloy 617 was evaluated by exposing both the as-received (AR) and GBE specimens in a salt-mixture of (75% Na2 SO4  + 20% NaCl + 5% V2 O5 ) at 1273 K for 24 h. The AR specimen having continuous network of random high angle grain boundaries (HAGBs) has undergone hot corrosion and substantial depletion/segregation of alloying elements through the entire cross section. The GBE specimen exhibited significantly reduced hot corrosion and depletion/segregation of alloying elements. This is attributed to the high fraction of 3-CSL triple junctions which break the percolation in the random HAGBs network.